2021
DOI: 10.3126/aej.v22i0.46807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Diversity Assessment of Nepalese Garlic (Allium sativum L.) Landraces

Abstract: A research was carried out at the field of National Agriculture Genetic Resources Centre (NAGRC), Khumaltar, Lalitpur, Nepal in 2019 with the objective of phenotypic characterization and genetic diversity assessment of thirty-seven local garlic landraces. The phenotypic diversity was assessed based on fifteen qualitative and nine quantitative characters by sing non replicated rod row design following the descriptors developed by IPGRI, 2001. Descriptive statistics were calculated by using MS Excel 2016 and UPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Generally, the lowest number of cloves per bulb was recorded from medium to large sized cloves. Similar observations were made by different researchers [17,10,21] who reported that clove size had significant effects on the number of cloves per bulb.…”
Section: Number Of Cloves Per Bulbsupporting
confidence: 88%
See 1 more Smart Citation
“…Generally, the lowest number of cloves per bulb was recorded from medium to large sized cloves. Similar observations were made by different researchers [17,10,21] who reported that clove size had significant effects on the number of cloves per bulb.…”
Section: Number Of Cloves Per Bulbsupporting
confidence: 88%
“…The lowest diameter of bulb (29.06 mm) was obtained from ARM 02 followed by ARM 05 (29.18 mm) (Table 3). Similar type of variation of bulb diameter of different genotypes was also reported by Researcher [21].…”
Section: Diameter Of Bulbsupporting
confidence: 87%
“…The diversity index ranged from 0.64 (Bulb structure type, and Disease) up to 1.13 (Vigour). All six qualitative traits have high diversity index (H ≥0.60) (Eticha et al, 2005) confirming high genetic diversity among the garlic landraces in terms of qualitative phenotypic traits (Simon & Jenderek, 2003;Pooler & Simon, 1993;Thapa et al, 2021).…”
Section: Resultsmentioning
confidence: 73%
“…Traditional varieties, also known as landraces, have highyield stabilityunder low-input agricultural systems and have the capacity to tolerate biotic and abiotic stresses despite having a lower yield than improved and hybrid varieties (Manohara et al, 2018). One of the primary causes of the low utilization of landraces is a lack of knowledge about particular characteristics of them (Thapa et al, 2021). In order to improve the use of specific traits in breeding programs, it is crucial to evaluate the diversity of wheat that is currently available.…”
Section: Introductionmentioning
confidence: 99%